Customers’ Perception of Service Quality and its Impact on Customer Loyalty - Kaur, Surjit; Kaur, Manpreet (Gyan Management Journal, 2014)
This paper studies the relation of service quality with customer loyalty and further analyzes its’ impact on customer loyalty. The data for the study has been collected from 228 customers visiting five ’A’ class hotels of Jammu city. The results revealed that there exists a positive relationship between service quality and customer loyalty and found that service quality predicts customer loyalty significantly. Tangibles, reliability and assurance dimensions of service quality have shown positive influence on customer loyalty. These findings provide considerable evidence for the need of improving different components of service quality in order to win over the loyalty of customers.